A Natural Glycyrrhizic Acid‐Tailored Light‐Responsive Gelator. Issue 9 (30th March 2018) - Fang, Heshu; Zhao, Xia; Lin, Yuan; Yang, Song; Hu, Jun
Abstract: The construction of stimuli‐responsive materials by using naturally occurring molecules as building blocks has received increasing attention owing to their bioavailability, biocompatibility, and biodegradability. Herein, a symmetrical azobenzene‐functionalized natural glycyrrhizic acid ( trans ‐GAG ) was synthesized and could form stable supramolecular gels in DMSO/H2 O and MeOH/H2 O. Owing to trans – cis isomerization, this gel exhibited typical light‐responsive behavior that led to a reversible gel–sol transition accompanied by a variation in morphology and rheology. Additionally, this trans ‐GAG gel displayed a distinct injectable self‐healing property and outstanding biocompatibility. This work provides a simple yet rational strategy to fabricate stimuli‐responsive materials from naturally occurring, eco‐friendly molecules. Abstract : Make light work of gelation : A symmetrical azobenzene‐functionalized natural glycyrrhizic acid ( trans ‐GAG ; see figure) was synthesized, and could form a stable light‐responsive supramolecular gel due to cis – trans isomerization. This work provides a simple yet rational way to fabricate functional materials from naturally occurring eco‐friendly triterpenes in light of their biocompatibility and biodegradability.